Staff Absenteeism in Public Health Facilities of Uganda: A Study in Bushenyi District on Contributing Factors - Nyamweya, Nancy Nyasuguta; Yekka, Peter; Mubutu, Ronny Drasi; Kasozi, Keneth Iceland; Muhindo, Jane (Open Journal of Nursing, 2017)
Staff absenteeism is a global challenge in health care service delivery that has not spared any country.This was to assess the factors contributing to staff absenteeism in public health facilities in Bushenyi District of Uganda. This was a cross sectional study conducted for a period of 3 months in which data were collected using a questionnaire and interviews. Majority of participants were females (66.4%) which 50% in the age of 31 - 45 years. The study showed that residing outside the health facility (42.1%) i.e. walking distances over 10 km to get to work was a challenge. Family conflicts, overstay in one workstation without rotations to other major health facilities and drug abuse as well as inadequate supervision were major contributing factors to absenteeism (P < 0.05). This is complicated by increased administrative duties coupled with poor enumeration and motivation in the health facilities visited. However over 50% of the participants reported never to have left their work stations without permission, thus showing that the challenges faced in a majority of health centers in rural communities warrant national support through improved motivation of staff working in the challenging communities. Staff absenteeism in rural communities is a major challenge that needs a multi-sectorial approach for its effective management, thus showing a need to revise policy in the health sector.
Keywords: Staff absenteeism in Uganda, Uganda Health Care, Nurses in Africa